Language based modeling for asynchronous discrete event systems - Uygur, Gürkan; Sattler, Sebastian (AmE 2016 - Automotive meets Electronics, 2019)
We present a language based modeling which is capable to preserve the requirements specification in different levels of abstraction. To warrant a unique map between the specification and its abstraction respectively substantiation (materialization) we choose a propositional syntax; the modeling succeeds by syntactically translating the specified requirements into its propositional terms. Our approach preserves the behavior as well as the structure of the specification. This is an essential bonus for design verification and test of asynchronous feedbacked discrete event systems. In this paper, we state the definition of our formal specification language, apply it to a use case and discuss its testability.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Abstraction; Asynchronous; Discrete event; Language; Pin partitioning; Requirement; Signal flow plan; Specification; Testability